2021
DOI: 10.3389/fonc.2021.782263
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Daily CT for EPID-Based Transit In Vivo Dosimetry

Abstract: PurposeThe difference in anatomical structure and positioning between planning and treatment may lead to bias in electronic portal image device (EPID)-based in vivo dosimetry calculations. The purpose of this study was to use daily CT instead of planning CT as a reference for EPID-based in vivo dosimetry calculations and to analyze the necessity of using daily CT for EPID-based in vivo dosimetry calculations in terms of patient quality assurance.Materials and MethodsTwenty patients were enrolled in this study.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 33 publications
(45 reference statements)
1
10
0
Order By: Relevance
“…The effect of systematic changes in patient anatomy, such as tumor progression and weight alteration after the time of simulation, is minimized due to speeding up of treatment preparation. This is particularly true for the first fraction, which can be inferred from the fact that in vivo dosimetry of the All‐in‐One solution demonstrates excellent γ passing rates compared with the routine workflow, as the in vivo result is sensitive to both patient‐related variations and machine‐related errors 20,23 . Over the course of therapy, dosimetrical benefits from the reduced time expended in RT preparation might be limited due to the existence of inter‐fractional uncertainties (such as treatment‐induced tumor shrinkage).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The effect of systematic changes in patient anatomy, such as tumor progression and weight alteration after the time of simulation, is minimized due to speeding up of treatment preparation. This is particularly true for the first fraction, which can be inferred from the fact that in vivo dosimetry of the All‐in‐One solution demonstrates excellent γ passing rates compared with the routine workflow, as the in vivo result is sensitive to both patient‐related variations and machine‐related errors 20,23 . Over the course of therapy, dosimetrical benefits from the reduced time expended in RT preparation might be limited due to the existence of inter‐fractional uncertainties (such as treatment‐induced tumor shrinkage).…”
Section: Discussionmentioning
confidence: 99%
“…In vivo dosimetry for online QA is available in this commercial system by measuring the exit dose from the patient using an amorphous silicon electronic portal imaging device (aSi‐EPID), and comparing with the TPS calculation by γ analysis based on patient anatomy using a Monte Carlo method. Prior to clinical implementation, the EPID detector response was corrected and calibrated for absolute dosimetry, and the accuracy of the transit dose calculation was validated by phantom measurement, as described in a previous study 20 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…EPIDs are present on modern linear accelerators, offering the possibility to perform patient position and dosimetric verification in 2D/3D, and automation [9] , [10] . Several studies have shown the sensitivity and effectiveness of EPID-based IVD (EIVD) for different treatment sites and relevant deviations encountered in clinical routine [11] , [12] , [13] , [14] .…”
Section: Introductionmentioning
confidence: 99%